2020
DOI: 10.1038/s41586-020-2076-4
|View full text |Cite
|
Sign up to set email alerts
|

A pathway coordinated by DELE1 relays mitochondrial stress to the cytosol

Abstract: PERK 1,2 . By contrast, the effects of CDDO on CHOP were not blunted by any individual EIF2α kinase deficiency (Extended Data Fig. 1g) , possibly owing to the limited specificity of related compounds 11 . The comparative interrogation of CHOP regulators following three distinct cellular insults allowed us to differentiate global regulators of CHOP biology (Extended Data Fig. 1h-m) from such selectively operating in the context of CCCP-induced mitochondrial depolarization (Extended Data Figs. 2-4). In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
347
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(372 citation statements)
references
References 46 publications
24
347
1
Order By: Relevance
“…More recent studies showed that mitochondrial stress causes the release of the DELE1 protein, which in turn binds and activates the HRI kinase (58,59). It would be of great interest in the future studies to determine whether Ant1 overloading induces eIF2 phosphorylation by the same mechanism, or by an independent pathway downstream of mPOS in the cytosol.…”
Section: Discussionmentioning
confidence: 98%
“…More recent studies showed that mitochondrial stress causes the release of the DELE1 protein, which in turn binds and activates the HRI kinase (58,59). It would be of great interest in the future studies to determine whether Ant1 overloading induces eIF2 phosphorylation by the same mechanism, or by an independent pathway downstream of mPOS in the cytosol.…”
Section: Discussionmentioning
confidence: 98%
“…Communication of mitochondrial respiration to mTORC1 may prevent mTORC1-mediated activation of anabolic processes, such as nucleotide synthesis, when TCA cycle-derived biosynthetic precursors, such as aspartate, are limiting. Impaired mitochondrial respiration has also been shown to activate ATF4 [21][22][23][24][25] , and there is accumulating evidence that ATF4 promotes transcription of genes that support respiration and relief of mitochondrial stress 24,25 . We show that exogenous asparagine is sufficient to rescue mTORC1 inhibition and ATF4 activation in the context of respiration impairment, which suggests that asparagine is a crucial cellular signal of mitochondrial respiration ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…be carried out in robotically controlled batch reactors integrated with liquid handlers, purification and analytical systems 6 . And a robotic system that uses conventional laboratory apparatus, such as round-bottomed flasks, and which uses a standardized approach (the 'chemputer') to translate chemical-synthesis methods into physical operations, was reported last year 7 .…”
mentioning
confidence: 99%
“…Environmental toxins 2 and disease-causing agents 3 , as well as diverse age-associated conditions, including Alzheimer's disease 4 and Parkinson's disease 5 , are linked to mitochondrial dysfunction. Now, Guo et al 6 (page 427) and Fessler et al 7 (page 433) report a previously unknown mechanism that is used by mitochondria to send a signal of their dysfunction to the cytosol and nucleus, enabling the cell to adapt to mitochondrial stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation